Khả năng hấp phụ crom(III) bằng vật liệu compozit polyanilin-lignin - Thanh, Nguyễn Ngọc; Phương Thảo, Bùi Thị; Hùng, Nguyễn Văn; Linh, Đường Khánh; Huyền Hải, Dương Thị; Nga, Nguyễn Thị; Thanh Vân, Trần Thị; Trung, Vũ Quốc (Vietnam Journal of Chemistry, 2016)
Polyaniline-lignin composite were prepared by polymerization of aniline in the presence of lignin using (NH4)2S2O8 as oxidant. Properties of the obtained polyaniline-lignin composite were studied by FT-IR spectra, thermal gravimetric analysis (TGA) and scanning electron microscopy (SEM). Results on absorption of Cr(III) by polyaniline-lignin composite showed the optimal absorption conditions of Cr(III) were pH of solution 5,0 and contact time of one hour. Absorption of Cr(III) followed the Langmuir model as evidenced by a good coefficient of correlation value (R2 = 0.9986). The maximum adsorption capacity, qmax from the Langmuir model was found to be 71.43 mg/g for Cr(III) and are higher than the separate polyaniline or lignin.